Cholera El Tor enteritis in Jakarta - Jeni Iswandari; Helena Erawan; S. Komalarini; Shinta Njotosiswojo (Paediatrica Indonesiana, 1973)
Gastrointestinal disturbances with symptoms of vomiting and diarrhoea, accompanied with acute dehydration, acidosis, sodium and potassium losses broke out in 1920 in Asia. This disease was called cholera Asiatica or classical cholera and was caused by "classical" cholera vibrios (Felsenfeld, 1966). It was also known in Europe. From 1923 to 1960 it subsided, but within this period a new type of cholera, cholera El Tor had made it appearance in Indonesia. In the Southern part of the island of Sulawesi, Indonesia, cholera EI Tor was detected for the first time by de Moor (Felsenfeld, 1966; Moor, 1963; Mukerjee and Basu, 1967). Cholera EI Tor is an endemic disease, which sometimes has its epidemic outbreaks. Sulawesi was considered endemic and the following epidemics occurred in 1939, 1944, 1957 and 1960 (Moor, 1963).